Raport werbalny i jego wykorzystanie w badaniach nad strategiami rozwiązywania testów z zakresu czytania - Konieczna, Anna (Neofilolog, 2019)
The article discusses kinds of verbal reports and their characteristic features. More specifically, it focuses on: a) the validity of particular types of verbal reports and the data these are likely to provide, b) a quite difficult distinction between introspection and retrospection in researching reading, and c) the characteristic features and limitations of think-aloud protocols (categorized as introspective verbal report), especially if used to investigate the concrete reading format of gapped-text.